ความหลากหลายของไม้ล้มลุก ไม้พุ่มและไม้เลื้อยตามเส้นทางศึกษาธรรมชาติเขาหลวง อุทยานแห่งชาติน้ำตกห้วยยาง จังหวัดประจวบคีรีขันธ์ - กาญจนา ลิมป์กิตติกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This study collected samples of herbs, shrubs, and climbers along Khao Luang nature trail, Huai Yang Waterfall National Park, Prachuap Khiri Khan Province, Thailand, from April 2014 to May 2015. At total number of 109 plant samples were collected. From these samples, 22 families, 58 genera, and 83 plant species were identified, which were 29 herbs, 31 shrubs, and 23 climbers. The family with the most abundant species was Rubiaceae, which comprised 21 species. The genus with the most abundant species was Jasminum (Oleaceae) consisting of 5 species. Among the identified species, 13 were endemic. Furthermore, 5 of these endemic species were vulnerable. The key to genus and key to species as well as the detailed descriptions of all families, genera, and species were provided. Plant samples were deposited at Bangkok Forestry Herbarium (BKF). In addition, the diversity of the species from the family Orchidaceae was compared with the previous study.